Multi-level governance and cross-sector practices supporting the European Union Strategy for the Adriatic and Ionian Region - Michalun, Maria Varinia (OECD Publishing, 2019)
European Union Strategy for the Adriatic and Ionian Region (EUSAIR) represents a long-term strategic policy framework to promote socio-economic growth and tighter relations between European Union member countries and countries in the Western Balkan region. Of the four European Union Strategies in place, EUSAIR is potentially the most challenging, with significant degrees of diversity among the four EU and four non-EU member partner countries. This is often revealed by their differences in administrative capacity, governance and economic development. National multi-level governance structures supporting EUSAIR contribute to the Strategy's national-level implementation. Enhancing the national multi-level governance practices applied to EUSAIR by participating countries could further build the Strategy's ability to contribute to national and macro-regional growth, development and environmental sustainability. This paper explores how questions of ownership, funding, strategic synergies, institutional coordination mechanisms, resource capacities and constraints, and stakeholder engagement affect EUSAIR implementation, and offers a series of recommendations for action
Keywords: Urban, Rural and Regional Development